Development of gold recovery technology from fine and ultrafine ground refractory sulfide concentrates - Olga Khmelnitskaya; Tatiana Chikina; Olga Lanchakova; Andrei Yevdokimov; Ivan Sidorov (International Mineral Processing Congress, 2014)
"The paper focuses on the results of the research on development of hydrometallurgical process of gold recovery from refractory sulfide flotation concentrates based on fine and ultrafine grinding. Refractory concentrates (the degree of refractoriness is 16.9%-82.6%) were chosen for testing. The efficiency of the process based on fine and ultrafine grinding to treat flotation concentrates with gold intergrown with sulfides and rock-forming minerals was shown. Based on the test work conducted, the process option was chosen. In included grinding of flotation concentrate to the size of 98% minus 20µm in a bead mill, lime treatment with air blow, CIL, filtration and detoxification of liquid phase of the slurry. This process (compared to the basic option) provides the recovery of gold from 82.6%, up to 94.0% and decreases the residual grade in the tailings from 3.3g/t to 1.1g/t at the consumption of 12.6NaCNkg/t. Based on the results of the test work and pilot plant testing, project design criteria of flotation circuit at a Russian plant was developed."